Influence of endometrial thickness on pregnancy rates in modified natural cycle frozen‐thawed embryo transfer. (24th April 2018) - Groenewoud, Eva R.; Cohlen, Ben J.; Al‐Oraiby, Amani; Brinkhuis, Egbert A.; Broekmans, Frank J. M.; de Bruin, Jan‐Peter; van Dool, Grada; Fleisher, Katrin; Friederich, Jaap; Goddijn, Mariëtte; Hoek, Annemieke; Hoozemans, Diederik A.; et al.
Abstract: Introduction: Pregnancy after frozen‐thawed embryo transfer (FET) is a multifactorial process. Although embryo quality is a key factor in determining pregnancy, other factors, including maternal determinants, are also considered to be predictive. Even though an association between endometrial thickness measured by transvaginal ultrasound and pregnancy rates has been reported in patients undergoing various assisted reproductive technology treatments, whether endometrial thickness predicts achieving pregnancy after natural cycle FET (NC‐FET) remains unclear. Material and methods: In this cohort study, 463 patients allocated to the modified NC‐FET (mNC‐FET) arm of a previously published randomized controlled trial were included. Monitoring in mNC‐FET cycles consisted of regular ultrasound scans, measuring both dominant follicle and endometrial thickness. When the dominant follicle reached a size of 16–20 mm, an injection of human chorionic gonadotrophin was administered and embryo thawing and transfer planned. No minimal endometrial thickness was defined below which transfer was to be deferred. The primary endpoint was ongoing pregnancy rate. Results: Overall, the ongoing pregnancy rate per started FET cycle was 12.5%. Multivariate regression analyses showed that embryo quality was the only significant predictor for ongoing pregnancy. Mean endometrial thickness did not differ between patients achieving ongoing pregnancy and those who did not (9.0 vs. 8.8 mm, p = 0.4). Comparable results were obtained with regard to clinical pregnancy, live birth and miscarriage rates. The area under the receiver operator curve was 0.5, indicating little discriminatory value of endometrial thickness. Conclusions: Given that endometrial thickness was not found to be predictive of pregnancy after mNC‐FET, cancellation based on endometrial thickness alone may not be justified.